Management of cervicofacial infections: a survey of current practice in maxillofacial units in the UK. Issue 9 (November 2017) - McDonald, C.; Hennedige, A.; Henry, A.; Dawoud, B.; Kulkarni, R.; Gilbert, K.; Kyzas, P.; Morrison, R.; McCaul, J.A.; ,
Abstract: Cervicofacial infections are common emergency presentations to maxillofacial departments in the UK, there is no consensus about their management and, in particular, the role of corticosteroids is not clear. Our aim was to find out the current practice of UK maxillofacial surgeons in managing these infections using a multicentre questionnaire study. The questionnaire was designed, piloted, and revised before distribution, and questions were asked to assess preoperative, operative, and postoperative management. It was distributed to maxillofacial surgeons throughout the UK through the Maxillofacial Research Trainee Collaborative (MTReC) network, and at the 2016 British Association of Oral and Maxillofacial Surgeons (BAOMS) Junior Trainees Group conference. A total of 350 questionnaires were distributed to 17 maxillofacial units. Eighty-six questionnaires were distributed at the BAOMS Junior Trainee conference. An overall response rate of 92% (n = 324) was achieved. The results showed that there were important differences in reported practice between and within maxillofacial units in the UK in managing these infections. The antibiotic regimens and use of steroids varied widely. Twenty-three per cent of respondents had to wait over 24 hours for access to emergency theatres. However, these results provide no hard evidence for or against the use of corticosteroids in cervicofacial infections.